Maternal obesity and breastfeeding intention, initiation, intensity and duration: a systematic review. Issue 2 (20th August 2012) - Turcksin, Rivka; Bel, Sarah; Galjaard, Sander; Devlieger, Roland
Abstract This systematic review investigates the relationship between maternal obesity and breastfeeding intention, initiation, intensity, duration and milk supply. A comprehensive search was performed through three major databases, including Medline, Cochrane Library and Cumulative Index For Nursing and Allied Health Literature, and by screening reference lists of the relevant publications. Selection criteria were: report of original research, studies on low‐risk obese mothers and the comparison with normal weight mothers which met at least two of the following primary outcomes: breastfeeding intention; initiation; intensity; duration and/or milk supply. Furthermore, the included reports had to contain a clear definition of pre‐pregnant obesity, use compensation mechanisms for potential confounding factors, have a prospective cohort design and had to have been published between 1997 and 2011 and in English, French or Dutch. Effects of obesity on breastfeeding intention, initiation, intensity, duration and milk supply were analysed, tabulated and summarised in this review. Studies have found that obese women are less likely to intend to breastfeed and that maternal obesity seems to be associated with a decreased initiation of breastfeeding, a shortened duration of breastfeeding, a less adequate milk supply and delayed onset of lactogenesis II, compared with their normal weight counterparts. This systematic review indicates therefore that maternal obesity is an adverse determinant for breastfeeding success.